ANALYSIS OF THE FACTORS THAT AFFECT THE ORIGINAL REGIONAL INCOME OF THE PROVINCE OF NORTH SUMATERA USING PANEL DATA REGRESSION - Saputri, Ika Junia; Dur, Sajaratud; Husein, Ismail (UIN Sumatera Utara, 2022)
Regional Own Revenue is all revenue from the government at the regional level in a certain period, usually in a period of one fiscal year. There are several factors that can be used to increase Local Own Revenue. The factors used in this study are gross regional domestic product, number of tourists and restaurant taxes. This research was carried out using panel data analysis which is a combination of cross-sectional data (Districts/Cities in North Sumatra) and also time series (Regional Original Income 2015-2020). The best model obtained is the random effect model. From the value of Regional Original Income and these three factors, it was found that the results of Regional Original Revenue in North Sumatra had increased in 2015-2018, but in 2019-2020 Regional Original Revenue in North Sumatra had decreased. The variable that has a positive effect and also has a significant effect on Regional Original Income is the restaurant tax variable. The R2 value of this model is 0.78634, which means that the ability of the Restaurant Tax variable to explain the Regency/City Local Revenue variable in North Sumatra Province is 78.634%, while the remaining 21.366% is explained by other factors not included in the model.